2019
DOI: 10.1371/journal.pone.0221159
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in innate responses and gene expression profiles in memory CD4 T cells are apparent very early during acute simian immunodeficiency virus infection

Abstract: Gender differences in Human immunodeficiency virus (HIV) disease progression and comorbidities have been extensively reported. Using the simian immunodeficiency virus (SIV) infected rhesus macaque model, we show that these differences are apparent very early during the course of infection. Though there were no major changes in the proportions of CD4 T cells or its subsets, central memory CD4 T cells from female macaques were found to differentially regulate a significantly larger number of genes at day 4 post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Sex differences in MCP-1/CCL2 have been found in macaques, with females having significantly higher levels of MCP-1/CCL2 in their plasma compared to their male counterparts during HIV infection. The elevated levels of MCP-1 in female macaques were surprising given the lower viral loads in HIV infected women reported in earlier studies [ 27 ]. One possibility is that difference observed between males and females in serum MCP-1 production following infection is due to sex-dependent differences in monocyte trafficking.…”
Section: Discussionmentioning
confidence: 87%
“…Sex differences in MCP-1/CCL2 have been found in macaques, with females having significantly higher levels of MCP-1/CCL2 in their plasma compared to their male counterparts during HIV infection. The elevated levels of MCP-1 in female macaques were surprising given the lower viral loads in HIV infected women reported in earlier studies [ 27 ]. One possibility is that difference observed between males and females in serum MCP-1 production following infection is due to sex-dependent differences in monocyte trafficking.…”
Section: Discussionmentioning
confidence: 87%
“…The sex-based difference in inflammation seems to be also set very early in the course of infection. In a nonhuman primate model, George et al [32] in 2019 not only showed that pathogenic sequelae seen during chronic infection was shaped early during the course of HIV infection but that female macaques already had significantly higher levels of pro-inflammatory cytokines as compared with their male counterparts day 4 postinoculation. Ultimately these female animals progressed faster to SHIV than their male counterparts [33].…”
Section: Discussionmentioning
confidence: 99%
“…— sex differences in SIV and HIV disease progression and morbidities between species, including altered expression levels of interferons and other immune response genes, 220 and differences in vaccine-induced antibody species and their functions in SIV-infected rhesus macaques; 221…”
Section: The Continued Need For Hiv/aids Vaccinesmentioning
confidence: 99%
“…significantly different transcriptome profiles in CD4 and CD8 cells between cynomolgus macaques and humans; 219 sex differences in SIV and HIV disease progression and morbidities between species, including altered expression levels of interferons and other immune response genes, 220 and differences in vaccineinduced antibody species and their functions in SIV-infected rhesus macaques; 221 differential expression of the α4β7 integrin in CD4 T-cells of different NHPs used in HIV/AIDS research, which are one of the major targets of infection and which affect the course and rate of progress of the disease; 222 differences in several interferon-induced transmembrane protein (IFITM) genes between different NHPs used in HIV/AIDS research and humans, which can restrict SIV/HIV infection and replication; 223 and species specificity of Nef and Vpu genes/proteins in overcoming restriction of SIV/HIV, mapped to just a small number of amino acids. 224 There have been a number of notable issues recently reported that could affect the translation of data from NHPs to humans, 225 namely that:…”
Section: The Continued Need For Hiv/aids Vaccinesmentioning
confidence: 99%